Pengaruh Kepuasan Kerja terhadap Organizational Citizenship Behaviour dalam Konteks Lingkungan Kerja Hybrid - Tanzilal Alafta An Miulfa; Laila Listiana Ulya (SENTRI: Jurnal Riset Ilmiah, 2026)
This study examines the relationship between job satisfaction and Organizational Citizenship Behavior (OCB) among employees working under a hybrid work system. The increasing implementation of hybrid work arrangements presents unique challenges related to communication, collaboration, and employee engagement, which may influence employees’ discretionary behaviors at work. This research employed a quantitative approach with a correlational design. The sample consisted of 134 hybrid employees from various industrial sectors in Indonesia, selected through online questionnaire distribution using an OCB scale developed by Aisyia (2009) and a job satisfaction scale adapted from Oktavian (2024), which was based on Gultom et al. (2020). Data analysis was conducted using the Spearman Rank correlation test due to the non-normal distribution of the data. The results indicate a positive and significant relationship between job satisfaction and OCB (ρ = 0.688; p < 0.05), suggesting that higher levels of job satisfaction are associated with stronger voluntary behaviors that support organizational effectiveness. Job satisfaction contributed 47.3% to the variance in OCB, while the remaining variance was influenced by other factors not examined in this study. These findings highlight the crucial role of job satisfaction in fostering extra-role behaviors among employees in hybrid work environments. The study provides empirical evidence that maintaining employee satisfaction remains essential despite reduced face-to-face interaction in hybrid settings. Therefore, organizations implementing hybrid work systems are encouraged to focus on strategies that enhance job satisfaction to promote positive work behaviors and sustain organizational performance.